Parathyroid Hormone Causes Endothelial Dysfunction by Inducing Mitochondrial ROS and Specific Oxidative Signal Transduction Modifications. (19th December 2018) - Gambardella, Jessica; De Rosa, Matteo; Sorriento, Daniela; Prevete, Nella; Fiordelisi, Antonella; Ciccarelli, Michele; Trimarco, Bruno; De Luca, Nicola; Iaccarino, Guido
Abstract : Vitamin D deficiency contributes to cardiovascular risk (CVR), with hyperparathyroidism advocated as a putative mechanism. Indeed, mounting evidence supports the hypothesis that parathyroid hormone (PTH) impairs endothelial function, even though mechanisms are not fully elucidated. The present study was designed to verify in vitro the ability of sustained exposure to PTH to cause endothelial dysfunction, exploring the underlying mechanisms. In bovine aortic endothelial cells (BAECs), we evaluated the effects of PTH exposure (0.1 nM–24 hours) on both endothelial response to vasodilators, such as bradykinin (Bk (30 nM)) and acetylcholine (Ach (1  μ M)), and angiogenic competence. Pretreatment with PTH impaired endothelial response to Bk but not to Ach, in terms of cytosolic calcium fluxes and NO production. In order to explore the underlying mechanisms, we assessed the production of total and mitochondrial ROS (tROS and mROS, respectively) in response to PTH (at 1 and 3 hours). PTH increased ROS generation, to an extent high enough to determine oxidation of Bk receptor B2. Conversely, the oxidation levels of M1 and M3 Ach receptors were not affected by PTH. A mROS selective scavenger (MitoTEMPO (5  μ M)) restored the endothelial responsiveness to Bk while the well-known antioxidant properties of vitamin D (100 nM) failed to counteract PTH-mediated oxidative stress. PTH determined mitochondrial calcium fluxes ([Ca 2+ ]mt ) and the mitochondrial calcium uniporter inhibitor Ru360 (10  μ M) reduced mROS production and prevented the PTH-mediated endothelial dysfunction. Angiogenic competence was evaluated as tubular formations in the endothelial Matrigel assay and showed a significant impairment in PTH-pretreated cells (0.1 nM–24 hours), despite the increase in VEGF transcriptional levels. VEGFR2 oxidation occurred in response to PTH, suggesting that even the impairment of angiogenesis was due to the ROS surge. These results indicate that PTH affects endothelial function through ROS production, driven by mitochondrial calcium overload. PTH-induced oxidative stress might act as signaling modifiers, altering specific pathways (Bk and VEGF) and preserving others (Ach).